Alley farming with Leucaena: Effects of short grazed fallows on soil fertility and crop yields - Atta-Krah, A.N. (Cambridge University Press, 1990)
Reports on the first four-year phase of a study of the long term effects on soil fertility and crop production of continuous cultivation (without trees), continuous alley cropping, and a rotation of alley cropping and fallow (with livestock) within Leucaena (Leucaena leucocephala (Lam) de Wit) alleys. Also reports Some observations on the management of the alley grazing system.